PENGARUH UKURAN PERUSAHAAN, LEVERAGE, PROFITABILITAS dan KOMISARIS INDEPENDEN TERHADAP MANAJEMEN PAJAK - Irmadina, Zahra Puji; Zulaecha, Hesty Ervianni; Hidayat, Imam; Rachmania, Dewi (Universitas Gajah Putih, 2022)
The purpose of this study was to determine the effect of firm size, leverage, profitability, independent board of commissioners listed on the Indonesia Stock Exchange (IDX). The time period used is 5 years, namely the 2017-2021 period. The population of this study includes all manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The sampling technique used purposive sampling technique. Based on the criteria that have been set in the period of 42 companies. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analytical method used is panel data regression analysis. The results showed that firm size had no significant effect on tax management, leverage had no significant effect on tax management and profitability had a significant effect on tax management, independent commissioners had a positive effect on tax management, and simultaneously firm size, leverage, profitability and independent commissioners were simultaneously Together they affect tax management.